2020
DOI: 10.1111/bdi.12973
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomized, placebo‐controlled pilot trial of atorvastatin for nephrogenic diabetes insipidus in lithium users

Abstract: Objective Lithium remains an important treatment for mood disorders but is associated with kidney disease. Nephrogenic diabetes insipidus (NDI) is associated with up to 3‐fold risk of incident chronic kidney disease among lithium users. There are limited randomized controlled trials (RCT) for treatments of lithium‐induced NDI, and existing therapies can be poorly tolerated. Therefore, novel treatments are needed for lithium‐induced NDI. Method We conducted a 12‐week double‐blind pilot RCT to assess the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Previously, a preliminary cross‐sectional study of 71 Li users has suggested the use of atorvastatin in treatment of Li‐NDI patients; Elie et al, 2015 ). Recently, we showed, that atorvastatin for 12 weeks (using a relative low dose in order to minimize side effects) did not significantly improve urine osmolality in patients with partial NDI (UOsm < 600 mOsm/kg) and the data suggested potential greater utility of atorvastatin in patients with more severe NDI (UOsm < 300 mOsm/kg; Fotso et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previously, a preliminary cross‐sectional study of 71 Li users has suggested the use of atorvastatin in treatment of Li‐NDI patients; Elie et al, 2015 ). Recently, we showed, that atorvastatin for 12 weeks (using a relative low dose in order to minimize side effects) did not significantly improve urine osmolality in patients with partial NDI (UOsm < 600 mOsm/kg) and the data suggested potential greater utility of atorvastatin in patients with more severe NDI (UOsm < 300 mOsm/kg; Fotso et al, 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“…Previously, a preliminary crosssectional study of 71 Li users has suggested the use of atorvastatin in treatment of Li-NDI patients; Elie et al, 2015). Recently, we showed, that atorvastatin for 12 weeks (using a relative low dose in order to minimize side effects) did not significantly improve urine osmolality in patients with partial NDI (UOsm < 600 mOsm/kg) and the data suggested potential greater utility of atorvastatin in patients with more severe NDI (UOsm < 300 mOsm/kg; Fotso et al, 2021). Since acute statin treatment, 1 h simvastatin treatment of LLC-AQP2 cells or BB rat slices as well as 6 h fluvastatin treatment of normal mice, have shown increased trafficking of AQP2 (Li et al, 2011;Procino et al, 2011), we tested the acute effects of statins in the mCCD c1l cell line.…”
Section: Discussionmentioning
confidence: 97%
“…This secondary analysis will assess serum calcium, thyroid stimulating hormone (TSH), and low-density lipoproteins (LDL) that were previously collected in the original RCT. LDL was previously reported in the original RCT [ 27 ]. Established literature and medical guidelines were used to determine which values were considered within normal ranges for all blood and urine tests [ 29 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of agents are already in use for other indications, and ligands of G protein‐coupled receptor have been investigated as potential drugs for NDI therapy. Secretin with or without fluvastatin, simvastatin and aminoglycosides has been investigated in preclinical and clinical studies, although none of these to date has been able to demonstrate clinically meaningful results 166–168 . Atorvastatin was investigated in a double‐blind, randomised, placebo‐controlled trial in patients on lithium therapy, but, when used at a dose of 20 mg day −1 , did not improve urinary osmolality compared to placebo over a 12‐week period 168 .…”
Section: Treatmentmentioning
confidence: 99%